Global, regional, and national burden of chronic kidney disease attributable to high sodium intake from 1990 to 2019 - Liu, Wei; Zhou, Lingyun; Yin, Wenjun; Wang, Jianglin; Zuo, Xiaocong (Frontiers in Nutrition, 2023)
Background High sodium intake is a crucial risk factor for the development and progression of chronic kidney disease (CKD). However, the latest global spatiotemporal patterns of CKD burden attributable to high sodium intake still remain unclear. We aimed to evaluate the level and trends of the CKD burden associated with high sodium intake according to sex, age, socio-demographic index (SDI), region, and country from 1990 to 2019. Methods Data on CKD burden attributable to high sodium intake from 1990 to 2019 were extracted from the Global Burden of Disease (GBD) Study 2019. The CKD-related deaths, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR) attributable to high sodium intake were estimated by age, sex, SDI, region, and country. The estimated annual percentage change (EAPC) was calculated to evaluate the secular trends of ASMR and ASDR of CKD attributable to high sodium intake from 1990 to 2019. We further explored the associations of SDI with the ASMR and ASDR of CKD attributable to high sodium intake. Results Globally, the number of CKD-related deaths and DALYs attributable to high sodium intake were 45,530 (95% UI: 12,640 to 93,830) and 1.32 million (95% UI: 0.43 to 2.8) in 2019, both twice as many as those in 1990. However, the ASMR and ASDR slightly grew, with an EAPC of 0.22 (95% CI: 0.16 to 0.28) and 0.10 (95% CI: 0.04 to 0.16), respectively. The age-specific numbers and rates of deaths, as well as DALYs of CKD attributable to high sodium intake, rose with age and were greater in males than in females. The rates of deaths and DALYs peaked in the >95 age group for both females and males in 2019. From 1990 to 2019, the trends of both age-specific rates of mortality and DALYs of CKD attributable to high sodium intake were down in people under 60, while in people over 60, the trends were the opposite. The burden of CKD attributable to high sodium intake in 2019 and its temporal trends from 1990 to 2019 varied greatly by SDI quintile and geographic location. The ASMR or ASDR showed a non-linear negative correlation with SDI at the regional level. The EAPC in ASMR or ASDR showed a markedly negative correlation with ASMR or ASDR in 1990, with a coefficient of −0.40. Nevertheless, the EAPC in ASMR rather than ASDR was positively correlated with SDI in 2019, with a coefficient of 0.18. Conclusion Our findings suggest that there are significant sexual and geographic variations in the burden of CKD attributable to high sodium intake and its temporal trends. Globally, the high sodium intake-caused CKD burden continues to elevate, posing a major challenge to public health. In response to this, strengthened and tailored approaches for CKD prevention and sodium intake management are needed, especially for elderly populations, males, and the population in the middle SDI regions.